Influence of Variation in Fibre Dimensions and Parenchyma Proportion on Sheet Properties in Bamboo - Singh, Man Mohan; Purkayastha, S. K.; Bhola, P. P.; Sharma, Laxmi (Indian Forester, 1971)
By testing hand sheets made from 32 mixtures of different fractions of a pulp of Dendrocalamus striclus, beaten to 250 ml. (C.S.F.), the effect of variations in fibre dimensions on strength properties have been investigated. Fibre length, determined from unbeaten pulp, accounts for 77 to 90 per cent of the variation in strength properties viz. breaking length, burst factor and tear factor. Other fibre characteristics viz. ratio of lumen width to fibre diameter and percentage of fibres with obliterated lumen, which also exhibit similar relationship with the strength properties, are highly correlated with fibre length. Parenchyma proportion shows a high negative correlation with the sheet properties. Fibre length and parenchyma proportion together account for 94 per cent of the variation in strength properties.